Relationship of Social and Lifestyle Factors with Central Fat Distribution Expressed by the Aggregate Fat Distribution Index - Suder, Agnieszka; Sokołowski, Andrzej (Anthropological Review, 2014)
Abdominal obesity is caused by several factors and the explanation of the level of its variability also depends on anthropometric indexes applied for its assessment. The aim was to determine the degree of explanation of the abdominal adiposity variation, presented by the aggregate fat distribution index (AFDI), through the socio-economic status and lifestyle. Subjects and methods: A cross-sectional population-based study was conducted on a sample of 259 healthy working males aged 20–30 from the city of Cracow, Poland. A full model was created using a stepwise backward regression with the social and lifestyle data as independent variables and the AFDI as a dependent variable. The AFDI was created by unitarization applied to selected characteristics of fat distribution which were transformed into [0,1] interval (without measurement unit) and then added and averaged to form a composite index. The highest autonomous influence on AFDI is ascribed to age (b=0.2456 p=0.000), level of motor fitness (b=–0.2392 p=0.000), leisure time physical activity (b=–0.1353 p=0.000) and being born in a rural area (b=0.1300 p=0.000). The variables explain 17% (R2=0.1667) of the variation of the central fat distribution. Variation of the abdominal adiposity was explained with the use of AFDI at the level close to the commonly applied indexes.